Faktor-Faktor Yang Mempengaruhi Kinerja Pegawai Di Dinas Pemberdayaan Perempuan, Perlindungan Anak, Pengendalian Penduduk Dan Keluarga Berencana (DPPPAPPKB) KotaMetro - Saifudin, Agung; Sugeng, Sugeng (Universitas Muhammadiyah Metro, 2022)
This study examines the factors that affect employee performance, including Locus Of control, Leadership Style, Organizational Culture, Work Facilities, at the Department of Empowerment Women, Child Protection, Population Control and Family Planning (DPPPAPPKB) Metro City. The analytical method used is quantitative research. The object of this research is an employee who works at the Department of PPPAPPKB Metro City. The total population is 48 respondents. Data collection techniques using literature study, interviews, observations and questionnaires. Data analysis techniques using SPSS 20 include test requirements test instrument requirements, test requirements analysis and test hypotheses. The conclusion is that the four variables simultaneously show significant and significant influence on employee performance, so in this case discussing the influence of Locus Of Control, leadership, Organizational Culture, Work Facilities, on Employee Performance can be very important related to productivity and progress of government agencies. Keywords : Locus Of Control, leadership, Organizational Culture, Work Facilities, on Employee Performance